2015
DOI: 10.2514/1.a33119
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic Retropropulsion Thrust Vectoring for Mars Precision Landing

Abstract: Landing heavier payloads with pinpoint precision on the surface of Mars is a known challenge for future missions to Mars. Supersonic retropropulsion has been proposed as a means to deliver higher-mass payloads to the surface, traditionally with the sole intent of deceleration. By adding range control capability during the supersonic retropropulsion maneuver by means of thrust vectoring, it has been found that a substantial amount of propellant can be saved in a precision landing scenario when compared with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In recent years, SpaceX has realized the recycling of the first stage through the retro-propulsion and attitude control technology of the launch vehicle, which effectively reduces the launch cost and the launch cycle and promotes the development of the reusable launch vehicle (RLV). But a certain amount of propellant is reserved for the reentry process, which results in the loss of carrier capability [2]. In this situation, the inflatable aerodynamic decelerator (IAD) is noticed gradually due to its small size, foldable, and lightweight [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, SpaceX has realized the recycling of the first stage through the retro-propulsion and attitude control technology of the launch vehicle, which effectively reduces the launch cost and the launch cycle and promotes the development of the reusable launch vehicle (RLV). But a certain amount of propellant is reserved for the reentry process, which results in the loss of carrier capability [2]. In this situation, the inflatable aerodynamic decelerator (IAD) is noticed gradually due to its small size, foldable, and lightweight [3].…”
Section: Introductionmentioning
confidence: 99%
“…SRP can also be utilized as additional control authority for precision landing. 17 Computational fluid dynamics tools have been shown capable of capturing major flowfield features, including unsteadiness, albeit at considerable computational expense. [13][14] Recent computational and experimental efforts have demonstrated that, in Mars relevant conditions, thrust requirements are sufficiently high to render the aerodynamic axial force contribution negligible.…”
Section: Introductionmentioning
confidence: 99%